Successful establishment of CRISPR-based genome-edited clonal cell populations from primary cells of buffalo, goats, and sheep - Priyanka Singh; Bosco Jose; Devika Gautam; Aseem Tara; Shreya Malhotra; Sacchinandan De; Manoj K. Singh; Naresh L. Selokar (Revista Científica)
Genome editing technology has great potential for precise DNA modification in mammalian cells. The ability to precisely generate the clonal population of CRISPR-edited geno-type is of great importance in gene function/ pathway analysis, drug discovery, and production of genome-edited animals. In the present study, we demonstrated an efficient method to generate CRISPR-edited single-cell clonal populations of farm animals, including buffalo, goats, and sheep. To generate clonal cell populations, the primary fibroblasts were established through explant culture and then electroporated with CRISPR/Cas RNPs targeted for the disrupted MSTN gene. We used a single-cell pickup method in which one cell was picked up using an ultra-fined glass capillary and transferred into each well of a 96-well plate. For promoting the growth of single cells, we used growth factor-supplemented media. After seeding a single cell to each well, the plate was kept undisturbed for 5-7 days, and then cell attachment rates were noted. We reported that the cell attachment rates for buffalo, goat, and sheep cells were 40%, 77.08%, and 83.67%, respectively. The proliferation rates were 70.83%, 75.67%, and 78.05% for buffalo, goat, and sheep cells, respectively. We noticed that cell attachment and proliferation rates were better in the case of goat and sheep cells; also, these cells exhibited less vacuolation compared to buffalo cells. In the present study, we generated 11, 20, and 20 single-cell clones of MSTN-gene-edited buffalo, goat, and sheep cells. In conclusion, our method can be efficiently used to generate genome-edited single-cell clones to harness the potential of CRISPR technologies in farm animals.